2009
DOI: 10.1007/s00467-008-1078-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Clara cell protein urinary elimination as a marker of tubular dysfunction

Abstract: Clara cell 16-kDa protein (CC16) is a protein expressed primarily by the bronchial cells. It is rapidly eliminated by glomerular filtration, reabsorbed almost entirely, and catabolized in proximal tubule cells. To date, normal values for urinary CC16 in healthy children have not been determined. We have studied 63 pediatric patients (mean age 8.17 +/- 3.91 years) and 31 healthy children (control group; mean age 8.83 +/- 3.65 years). In the control group, the CC16/creatinine ratio was 1.22 +/- 1.52 microg/g. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Even though, after adjustment for specific gravity, we had a log-normal distribution of concentrations, assigning all of these censored data the same value, likely decreased the power of our analysis. The urinary levels of CC16 in our study are within the range of what has been reported in the few other studies that have measured CC16 in healthy children’s, as well as in asthmatic children’s, urine [ 14 , 46 , 47 ]. In the future, studies should use an ELISA kit with a lower limit of detection, as was recently reported by Ma and colleagues [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…Even though, after adjustment for specific gravity, we had a log-normal distribution of concentrations, assigning all of these censored data the same value, likely decreased the power of our analysis. The urinary levels of CC16 in our study are within the range of what has been reported in the few other studies that have measured CC16 in healthy children’s, as well as in asthmatic children’s, urine [ 14 , 46 , 47 ]. In the future, studies should use an ELISA kit with a lower limit of detection, as was recently reported by Ma and colleagues [ 14 ].…”
Section: Discussionsupporting
confidence: 88%
“…Dysfunction of the proximal tubule cells can cause diminished resorption of CC16 and its increased levels in urine. CC16 has been reported as a marker of proximal tubular dysfunction in adult [ 26 ] and child patients [ 27 ]. This protein marker is sensitive to very subtle defects in proximal tubular dysfunction that may not be detected by assay of classical urinary low-molecular-weight proteins [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our first paper on the subject, the value of the urinary CC16-to-creatinine ratio was zero in 16 of the 31 control children (51.6%) [12]. In another recent study by our group [13], the average urinary CC16-to-creatinine ratio in control children (1.12 ± 0.59 μg/g) ( n = 28) was even lower than that in the first study (1.22 ± 1.52 μg/g).…”
mentioning
confidence: 99%